‘Meteor’ as the First Official Łódź-Based Literary Group - Krawczyk, Alicja (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The article is devoted to the first Łódź-based literary group called ‘Meteor’, which operated in 1928-1930. The author mainly focuses on providing a reliable discussion of the circumstances of the establishing of the group by its founders, i.e. Grzegorz Timofiejew, Marian Piechal, and Kazimierz Sowiński, and a careful specification of its programme. She also interpreted the Meteor’s works, i.e. revolutionist literary texts published in the Czasopismo Poetyckie Meteor, created by the members of the group.